Complications Following Anorectal Surgery - Kunitake, Hiroko; Poylin, Vitaliy (Clinics in Colon and Rectal Surgery, 2016)
Anorectal surgery is well tolerated. Rates of minor complications are relatively high, but major postoperative complications are uncommon. Prompt identification of postoperative complications is necessary to avoid significant patient morbidity. The most common acute complications include bleeding, infection, and urinary retention. Pelvic sepsis, while may result in dramatic morbidity and even mortality, is relatively rare. The most feared long-term complications include fecal incontinence, anal stenosis, and chronic pelvic pain.
Keywords: anorectal surgery; complications; hemorrhage; urinary retention; pelvic sepsis